URGENSI PENDIDIKAN MORAL ISLAMI DI ERA GLOBAL - E. Kosmajadi (MADINASIKA, 2019)
The research aims to study in a descriptive manner the urgency of Islamic moral education in the global era and solutions to overcome it. Many facts that have been revealed about the low morality of the people cause concern for the loss of national identity. Indications that appear in the form of rampant fraud, crime, prostitution, pornography, trafficking in persons, the spread of hoaxs and various other forms of social-ethical violations. The rapid progress of information and communication technology adds to the difficulty of filtering out foreign cultures that are not relevant to the character of the Indonesian people. The way to anticipate it is needed to strengthen internal morality, in the form of more intensive Islamic moral education. The research method uses library research with a qualitative-interpretative analysis approach, the main data being core principles in Islamic moral education. The results showed: 1) Throughout life, humans need education; 2) Moral education is the core of forming moral character; 3) In the global era, moral education is absolutely essential and cannot be delayed